East Asian "miracle" versus dismal Latin American development: State autonomy matters - Žeruolis, Darius (Politologija, 1997)
The essay examines causes of spectacular East Asian economic growth and contrasts them to the cyclical and unimpressive Latin American developmental performance in 1960s-1980s. In the paper, analytical research strategy is based on John Stuart Mill's comparative "method of difference," i.e., maximisation of variance in the dependent variable (ideally selecting the opposite outcomes) and grouping of countries on this basis. The main point of the essay is that state autonomy as a composite variable of structural, institutional, and strategic factors (independent variable) explains differences in economic development (dependent variable) in two sets of countries. Argentina and Brazil clearly underperformed, while South Korea and Taiwan grew impressively during the above-mentioned period. Occasionally, however, the paper glances at other developing countries as well, in order to have a broader analysis of causal arguments. For example, while culturally the two sets of countries differ, it has proved difficult to sustain the cultural argument to explain developmental superiority—Confucian culture over Spanish or Portuguese cultures—when the sample is enlarged spatially (e.g., to explain China in that period) or temporarily (to explain Taiwan or South Korea before 1945). Likewise, typology of economic systems (liberal vs. state-dominated) and regime types (democratic vs. non-democratic) alone could not solve the comparative problem because they failed "extended tests" and contradicted empirical evidence.The paper provides a definition of autonomous state which can be briefly summarised as a strong state (in terms of extraction of resources) in control of society and efficient allocation of developmental resources (investments, labour, administration) to benefit the country in the long run. Then the essay moves on to regional analysis of these indicators to explain these "prerequisites" historically and at the time when the developmental paths of East Asian and Latin American countries diverged, i.e., in the mid-1950s to early 1960s. The implications of the primary import substitution industrialisation (ISI) are given a lengthier discussion. The essay concludes by comparing "options" for Latin America to forgo the trap of dependency theory-based policy formulation at the beginning of the secondary ISI phase and whether the East Asian path can be, or could have been, repeated elsewhere.
Keywords: -